The effects of portfolio assessment on writing of EFL students - Tomalá Guzman, Ingrid (2025)
This study analyzes the effects of portfolio assessment on the development of writing skills in students learning English as a Foreign Language (EFL). Given the importance of language skills in academic and professional contexts, the portfolio is presented as an educational tool that supports the gradual and reflective development of writing, one of the most complex skills to acquire. Through introspective activities guided by the teacher, students find relevant content to write about, which enhances their autonomy and creativity. The research, with a qualitative approach, was conducted through observations, interviews, and analysis of written productions. Results show that 85% of students improved their writing autonomy, while 78% of teachers reported a better understanding of their students' needs. Portfolio use also allows for continuous and personalized formative assessment, promoting the application of metacognitive strategies that help plan, manage, and evaluate the writing process. In conclusion, the study proposes replacing traditional assessment methods with portfolio use, as it encourages critical thinking, self-reflection, and the adaptation of pedagogical practicesto improve EFL writing instruction.